A Comparative Effectiveness Analysis of The Users of Public Transportation and Private Transportation for Employees: A Case of Cinere-Lebak Bulus Route - Rizak Agri Agustino; Andri Irfan Rifai; Susanty Handayani (International Journal Labs, 2022)
The use of private transportation or city transportation to get to work is an option for employees. Today, the use of private vehicles is still a favorite of employees with various considerations. This paper aims to determine the factors that influence employees from Cinere to the Lebak Bulus area to choose transportation between private vehicles and local public transportation (Angkot). The method used was to spread the questionnaire to respondents, who then analyzed the data of the questionnaire results using the radar chart method. The comparative research between private vehicles and city transportation shows that the variable strongly affects employees and workers from Cinere to the Lebak Bulus area in choosing a private vehicle transportation mode, namely the comfort variable.